2018
DOI: 10.3354/ab00698
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological diversity in sympatric kelps with contrasting reproductive strategies

Abstract: The evolution of asexual reproduction is considered a response to environmental conditions where it incurs less cost than sexual reproduction, maintains adapted genotypes and allows rapid proliferation into new areas. In rare circumstances, some species have evolved distinct asexual morphs or lineages in response to ubiquitous environmental conditions. Understanding the implications of, and the mechanisms underpinning, such reproductive strategies will be important for assessing the vulnerability of population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…It is a perennial species with an alternation of generations life cycle with macroscopic sporophytes (sampled here) alternating with microscopic gametophytes 30 . E. radiata does not reproduce asexually, except for the distinctive E. brevipes morphotype in Hamelin Bay 34 which was not sampled here. Samples of E. radiata sporophytes for genetics were collected across 800 km of coastline that experienced the highest thermal anomalies during the heatwave (up to 5.5 °C at Jurien Bay, Fig.…”
Section: Methodsmentioning
confidence: 79%
“…It is a perennial species with an alternation of generations life cycle with macroscopic sporophytes (sampled here) alternating with microscopic gametophytes 30 . E. radiata does not reproduce asexually, except for the distinctive E. brevipes morphotype in Hamelin Bay 34 which was not sampled here. Samples of E. radiata sporophytes for genetics were collected across 800 km of coastline that experienced the highest thermal anomalies during the heatwave (up to 5.5 °C at Jurien Bay, Fig.…”
Section: Methodsmentioning
confidence: 79%
“…Theoretical models predict that when clonality predominates, it will increase heterozygosity (Marshall & Weir, 1979;Balloux et al, 2003;De Meeûs et al, 2006), which may ultimately lead to higher levels of observed heterozygosity (Ho) than those expected (He) under panmixia. This deviation has been observed empirically through negative values of fixation index FIS, reported in various partially clonal populations (in animals Adjeroud et al, 2014; angiosperms Alberto et al, 2002;Alberto et al, 2005;, and red and brown macroalgae Guillemin et al, 2008;Ardehed et al, 2015;Coleman & Wernberg, 2018, Pardo et al, 2019. Without sex, alleles do not segregate independently, which implies that heterozygosity can be preserved rather than reduced over generations (Judson & Normark, 1996).…”
Section: Introductionmentioning
confidence: 75%
“…The risk associated with restoring populations in the absence of empirical genetic knowledge is that restored populations will inadvertently lack diversity or appropriate adaptive capacity to cope with extant or future conditions (e.g., Williams, 2001), which may be particularly pertinent for species that exhibit small scale dispersal and are therefore susceptible to reduced gene flow, increased inbreeding or asexual propagation (e.g., Guillemin et al, 2008;Coleman et al, 2011aColeman and Wernberg, 2018;Miller et al, 2019). This risk is exacerbated given increasing habitat fragmentation and deterioration often characterizes the seascapes from which donor adults or propagules must be sourced for restoration (Coleman and Kelaher, 2009).…”
Section: Recover -Restoration That Replicates Unknown Genetic Baselinesmentioning
confidence: 99%